"A Man Is Practically the General Norm" – A Case Study of Gender Inequality and Whiteness in the Classical Music Scene in Finland. Issue 1 (2nd January 2023) - Ramstedt, Anna
ABSTRACT: In this article I show how generally accepted forms of performance practice and performances by generally idealized performance figures reveal gendered and racialized imaginaries that prevail in the Finnish classical music culture. The research material for this article was gathered through thematic in-depth interviews with fourteen white cis women professional Finnish classical pianists, violinists, violists, and cellists between the ages of 25 and 45. I ask how gendered and racialized constructions are conveyed in performance ideals maintained by widely acclaimed performers and traditionally accepted ways of performing musical works. Further, I ask how gendered and racialized constructions associated with idealized performers and performance ideals shape, intertwine in, and influence the embodied experience of Finnish women musicians. I argue that the performers that are widely seen as quintessential form a canon of performers, that have a crucial role in maintaining the oppressive status quo of classical music by reaffirming and maintaining the idealized aesthetics through the very fleshy act of performing Eurocentric, gendered and racialized social imaginaries. These social imaginaries partly shape musicians' embodied subjectivity and affect their self-esteem as well as their understanding of gendered and racialized bodies, and their social value.